IMPERATIVE SENTENCE TO INDONESIAN LEARNERS THROUGH TOTAL PHYSICAL RESPONSE (TPR) METHOD - Ali, Sulpadli; Dj, Muhammad Zuhri; Musfirah, Musfirah (DIDAKTIKA, 2022)
The teachers are expected to be able to create an interesting and appropriate technique, learning style and method in EFL classroom. A study entitled Teaching Imperative Sentence Through TPR Method at the eighth grade learners of Ma’had Al-Junaidiyah Biru especially to young learner is aim to elaborate how the researchers him self applied TPR method in teaching imperative sentence. This study employed a qualitative method and was conducted in one of Islamic boarding school in Bone. The eighth grade learners were the subject of this study. To obtain the data a classroom observation and interview both the English teacher and the eighth learners were conducted. The findings revealed that the researchers applied three steps of TPR method they are; pre-teaching, whilst-teaching and post-teaching. The researches gave some commands and instructions based on the topic of each meeting for three-time meetings the learners responded physically as instructed. Moreover, they gave appropriate responses and fully enthusiasm to the researchers’ instructions. Additionally, the researchers provided some games and physical moves that young learners like for each meeting in order to support the TPR method so the learners will be more interested and enjoyable the EFL classroom situation and it is able to motivate the learners to learn English vocabulary.Keywords: Indonesian young learners, physical moves, TPR method, vocabulary